“We need to write with love”: Welty’s Political View during the Civil Rights Years - Almeida, Diana (2014)
This essays applies Eudora Welty’s theoretical remarks about the reading process, namely those presented in the essay “Must the Novelist Crusade?”, to one of the short stories she wrote during the Civil Rights movement, “The Demonstrators”. I argue that the writer adopts a compassionate, non-violent approach to the racial crisis especially acute in the Southern states, based on the belief that the political arena is concomitant with the individual sphere.